Earth Restoration from a Qur’anic Perspective: An Analysis of Imar al-Ard in Light of the Environmental Ethics of Aldo Leopold and Paul Taylor - Eni Zulaiha (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This research explores the ecological crisis in Indonesia caused by uncontrolled land conversion, such as deforestation for housing, industry, mining, and palm oil plantations. Every five seconds, the world loses a forest area equivalent to a football pitch, with Indonesia recording the second largest loss of primary tropical forest globally. This phenomenon not only leads to climate instability and natural disasters but also triggers economic shifts and a human spiritual crisis. The urgency of this research lies in the lack of Islamic discourse specifically addressing land conversion as a theological issue that touches on ethical and practical aspects. The aim of this study is to examine the concept of isti’mar (prospering the earth) in the Qur’an as a theological mandate for humanity to restore environmental balance. This qualitative research employs a thematic interpretation approach, integrating Aldo Leopold's land ethic environmental theory and Paul W. Taylor's biocentrism. The findings indicate that isti’mar demands a paradigm shift from human dominance to a partnership relationship with nature. This study proposes an Ecological Restoration Movement through two approaches: renaturalisation, which involves restoring land to its natural condition, and ecological adaptation as compensation for irretrievable land changes. In conclusion, isti’mar serves as a theological foundation for ecological restoration, guiding humanity in fulfilling its role as a steward of the earth through moral and ethical land management.